PROTECTION FOR CHILDREN WITH MOTHERS AS PRISONERS IN CORRECTIONAL INSTITUTIONS - Andriawan; Rodliyah; Wulandari, Laely (Lex Journal : Kajian Hukum dan Keadilan, 2019)
This research discusses the protection efforts of children who are included by their mothers who are prisoners in the class III Mataram women’s correctional institution. The main focus of the research is to find out the implementation of legal protection of children’s rights, as well as the obstacles faced in efforts to fulfill children’s rights in the correctional environment. The problem approach that will be used to discuss the problems in this research is a sociological juridical approach. The approach is carried out based on the main legal material to examine the theory, as well as legislation and observations or observations related to this research. The results show that although there are policies and service standards that support child protection, their implementation in the field still faces various challenges. These challenges include limited facilities, a lack of administration, and a lack of coordination between relevant agencies. This research emphasizes the importance of strengthening the protection system and cross-sector collaboration to ensure the fulfillment of children’s rights in correctional institutions.